Studi Komparasi Hari Raya Galungan di Bali dan Wijaya Dasami India - Etika, Tiwi - (Dharma Duta, 2022)
Galungan is a Balinese holiday, celebrating the victory of dharma (virtue) over adharma (evil). It is similar to Wijaya Dasami (Wijaya Dashami) and Durga Puja Nawaratri in India, celebrated by Hindus in other parts of the world. The word Dussehra is a variant of Dashahara which is a compound Sanskrit word meaning "ten days". Dus has the meaning "bad, evil, and sinful" and Hara means "removing, destroying", connoting "removing the bad, destroying the evil, sinful. In most of northern and western India, Dasha-Hara (literally, ten days) is celebrated in honor of Rama. Vijaya Dasami is observed after Navratri, on the tenth day, marked by a great procession where the clay statues are ceremoniously walked to a river or ocean coast for a solemn goodbye to Durga. This type of research is qualitative with a comparative study method. Collecting data using literature study, expert interviews, and Focus Group Discussion (FGD). Data analysis using Ethnographic Content Analysis (ECA). This festival is an old tradition of Hindu Dharma, though it is unclear how and in which century the festival began. Surviving manuscripts from the 14th century provide guidelines for Durga puja, while historical records suggest royalty and wealthy families were sponsoring major Durga puja public festivities since at least the 16th century. This article discusses a comparative study of Galungan Day in Bali and Wijaya Dasami in India which has the same essence, namely celebrating the victory of Dharma against Adharma. Keywords: Galungan, Wijaya Dasami, Hindu Festival Galungan adalah hari libur Bali, merayakan kemenangan dharma (kebajikan) atas adharma (kejahatan). Mirip dengan Wijaya Dasami (Wijaya Dashami) dan Durga Puja Nawaratri di India, yang dirayakan oleh umat Hindu di belahan dunia lain. Kata Dussehra adalah varian dari Dashahara yang merupakan kata majemuk Sansekerta yang berarti sepuluh hari. Dus berarti buruk, jahat, dan berdosa dan Hara berarti menghapus, menghancurkan, yang berarti menghilangkan keburukan, menghancurkan yang jahat, berdosa. Di sebagian besar India utara dan barat, Dasha-Hara (secara harfiah, sepuluh hari) adalah dirayakan untuk menghormati Rama. Vijaya Dasami dirayakan setelah Navratri, pada hari kesepuluh, ditandai dengan prosesi besar di mana patung-patung tanah liat dengan upacara berjalan ke sungai atau pantai laut untuk mengucapkan selamat tinggal kepada Durga. Jenis penelitian ini adalah kualitatif dengan metode studi komparasi. Pengumpulan data menggunakan studi kepustakaan, wawancara ahli dan Focus Group Discussion (FGD). Analisis data menggunakan Ethnographic Content Analysis (ECA). Festival ini adalah tradisi lama Hindu Dharma, meskipun tidak jelas bagaimana dan di abad mana festival dimulai. Manuskrip yang bertahan dari abad ke-14 memberikan pedoman untuk puja Durga, sementara catatan sejarah menunjukkan bahwa bangsawan dan keluarga kaya mensponsori perayaan umum puja Durga sejak setidaknya abad ke-16. Artikel ini membahas studi komparasi Hari Raya Galungan di Bali dan Wijaya Dasami di India yang memiliki esensi yang sama yaitu merayakan kemenangan Dharma melawan Adharma. Kata kunci : Galungan, Vijaya Dasami, Hari Raya Hindu